(untitled) (CSIAM Transactions on Applied Mathematics, 2025)
In our advanced modern world, ensuring the availability and access to freshwater resources remains a significant global challenge. Seawater desalination is viewed as one of the most promising solutions to address the increasing human demand for freshwater. This study theoretically examines the thermodynamics of a novel desalination system that integrates a copper sulfide (CuS) nanomaterial-porous membrane solar absorber for freshwater production. The governing partial differential equations for energy and mass balance in the model were derived from conservation laws and solved numerically using the method of lines. The impact of various parameters on steam temperature and freshwater production rate was analyzed in two scenarios: (i) under constant solar radiation flux in a controlled laboratory setting, and (ii) as a time-dependent function under typical daily solar radiation conditions. The pertinent results were presented graphically and discussed. It was found that the Nusselt number at the surface of the porous membrane solar absorber increases with the infusion of CuS nanomaterial. The desalination system reached a steady state with steam temperature, and the rate of freshwater production improved as the volume fraction of CuS nanomaterial in the porous membrane solar absorber increased. Additionally, an increase in steam generation and condensation Biot numbers further boosted the freshwater production rate.